Contribution to the faunistical list of Trichoptera (Insecta) of Serbia - Živić, Ivana (Acta entomologica slovenica (Ljubljana), 2006)
The faunistical list of Trichoptera of Serbia is revised. An increase in the number of species is a consequence of investigation of Trichoptera larvae in highland rivers of Serbia. The number of species found has risen from 173 to 186. Three genera and 13 species are new to the fauna of Serbia. Three specieshave been added as a result of examination of material in the museum collections: Rhyacophila stankovici Radovanović, Potamophylax (Stenophylax) rotundipennis Brauer and Potamophylax latipennis Curtis. Rhyacophila dorsalis Curtis is deleted from the list, and replaced with allopatric species R. nubila Zetterstedt. One species (Stenophylax latipennis) and one subspecies (Stenophylax vibex speluncarum) have been omitted due to misidentification andinsufficient data. The species Drusus serbicus Marinković is endemic in Serbia, while Crunoecia bosniaca Marinković-Gospodnetić, Rhyacophila bosnica Schmid and Rhyacophila vranitzensis Marinković et Botosaneanu are endemic species of the western Balkans.
Keywords: entomologija; insekti; mladoletnice; Serbia; Srbija; Trichoptera